Synergistic antimicrobial activities of phenolic-rich extract derived from olive pomace and UV-A light against bacterial pathogens and their biofilms - Yoonbin Kim; Woo-ju Kim; Selina C. Wang; Nitin Nitin (Current Research in Food Science)
Decontamination of surfaces in food handling and processing environments is a key food safety requirement. In this study, an antimicrobial phenolic-rich aqueous extract derived from olive pomace was combined with UV-A light for the inactivation of bacterial pathogens and their biofilms formed on a plastic surface. The potential antimicrobial synergism between OPE and UV-A light was evaluated against Escherichia coli O157:H7 and Listeria innocua and quantitatively assessed using isobologram analysis. In addition, the antimicrobial mechanisms and antibiofilm potential of the combined treatment were evaluated. The results demonstrated that OPE and UV-A light exhibited strong synergistic activities (interaction index [γ] < 1) and achieved more than a 5-log reduction of planktonic E. coli O157:H7 and L. innocua cells within 30 min, respectively. Among the major phenolic components of OPE, 4-hydroxyphenylacetic acid (4-HPA) and hydroxytyrosol (HT) exhibited strong synergistic activities with UV-A light. Mechanistic studies revealed that the combined treatment of OPE and UV-A light synergistically induced oxidative stress, membrane damage, and metabolic inhibition in bacterial cells. Furthermore, the combined treatment effectively inactivated bacterial biofilms formed on plastic surfaces and achieved more than a 5-log reduction of E. coli O157 and L. innocua biofilms within 60 min, respectively. Overall, the findings of this study highlight the strong synergistic potential of diverse phenolic compounds in OPE and UV-A light as an effective intervention strategy. This study provides valuable and practical insights into leveraging antimicrobial extracts derived from agricultural byproducts in combination with mild food processing technologies to enhance the microbial safety of food handling and processing environments.